The methodological establishment of the research aimed at the exploration of health condition and health behavior of educators working in early childhood education (Training and Practice : Journal of Educational Sciences, 2019)
The research of health condition and health behavior of Educators working in Early Childhood Education has been a neglected area until recently. However, because of their being role models, the exploration of this field is of high priority. During our cross-sectional, quantitative research 1,010 kindergarten teachers, infant educators, nurses and teaching assistants were examined. According to our findings we can see that the health behavior of the participating teachers is more positive than the population as a whole. On the other hand, a relatively large proportion of them suffer from chronic diseases like back-, waist- and other joint problems, which can be related to the higher physical strain caused by their working environment.